Capital Controls and Trade Liberalization in a Monetary Economy - Jang, B. (Washington, D.C. : International Monetary Fund, 1999)
This paper reexamines Aizenman's (1985) results on the effects of capital controls during unanticipated trade liberalization using an intertemporal optimizing monetary model. Unlike in Aizenman's model, which is based on the currency substitution model, foreign money is an interest-bearing asset in this paper, and its major role is to smooth intertemporal consumption. With this modification, Aizenman's results are reversed, thus showing that the effects of capital controls during trade liberalization would vary greatly depending on the role of foreign money in a country. The effects of an anticipated trade liberalization are also studied.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet